Healthy nutrition in secondary prevention after myocardial infarction. What to focus on? - O. L. Barbarash; D. Yu. Sedykh; T. S. Petrova; V. V. Kashtalap; D. P. Tsygankova (Кардиоваскулярная терапия и профилактика, 2022)
Rationalization of dietary behavior in patients after myocardial infarction is the subject of numerous discussions. Despite the proven preventive effect of a healthy diet and the benefits of certain foods in cardiovascular diseases, this type of intervention is still underused. The aim of this review was to analyze current approaches to modifying the nutrition of patients within the secondary prevention of myocardial infarction. For this, 903 publications from PubMed/MEDLINE database over the past 5 years were studied. The Mediterranean diet demonstrated the highest efficacy and safety in preventing athero-thrombotic events among existing dietary patterns. However, its wide reproducibility in different regions is associated with a number of limitations. Government programs to modify and support a healthy diet beyond the conventional low-cholesterol diet may be promising in secondary prevention, especially if patients are properly monitored and motivated.